A1.80 Alterations in gait profile and bone marrow inflammation before the onset of collagen-induced arthritis. (31st January 2014) - Sinn, K; Aschauer, C; Shvets, T; Niederreiter, B; Smolen, J; Redlich, K; Hayer, S
Abstract : Background: Chronic inflammation of joints ulimatively leads to bone and cartilage damage resulting in functional impairment or even complete disabilities of joints in RA patients. Purpose: (I) To assess objective, quantitative functional impairment in joints in collagen-induced arthritis, we performed longitudinal CatWalk-assisted gait profiles from mice before the onset and during the course of collagen-induced arthritis. (II) To address preclinical inflammatory changes before the onset of arthritis based on altered gait profiles. Material and Methods: Mice were immunised i.d. with bovine type II collagen (100µg) in presence of CFA in 8 week old male DBA1/J mice. After 3 weeks mice were boosted i.p. with type II coll (100µg) in PBS. CatWalk-assisted gait profiles were performed from immunised and non-immunised animals on day 14, 22, 27, 29, 33, 37, 41, 43 and 70 after first immunisation. Body weight and clinical signs of arthritis including paw swelling and grip strength were also evaluated at these time points. To assess inflammatory joint damage, we quantitatively assessed the extend of synovial inflammation, subchondral bone erosion and cartilage damage on hematoxylin & eosine (H&E), tartrate-resistant acid phosphatase (TRAP) and toluidine-blue stained paw sections at preclinical stages, d7, d14 and d40 after the boost injection. Neutrophil accumulation was analysed by immunohistochemical staining of hind paw sections. Results: To assess functional impairment, we established CatWalk-asssisted gait profiles during the course of the disease ranging from the day 14 until day 70 after the first immunisation. Expectedly, we observed significant changes in various gait parameters including print length, maximal intensity, … in front and hind paws during the acute phase of the disease. Most of the parameters show subsequent decline in the chronic phase the disease. Next, to evaluate alterations in gait profiles before the onset of clinical signs of arthritis, we assessed gait profiles every 2 nd day after the boost injection. Of note, we found significant changes in individual parameters including maximum contact area (mm 2 ), maximum contact max intensity, print width and print area even before the onset of paw swelling (1-3 days before). Histological analysis of hind paws from this preclinical stage revealed bone marrow accumulations of immune cells, in particular neutrophil granulocytes, but no obvious synovial hyperplasia or infiltration of immune cells into the synovial membrane. Conclusion: Functional impairment assessed by video-based Catwalk gait analysis occurs before the onset of clinical signs of arthritis and is linked to neutrophil accumulations in the bone marrow.